PENGARUH MULTILINGUALISME DALAM DUNIA PENDIDIKAN TERHADAP NASIONALISME PESERTA DIDIK DAN KAIDAH BAHASA INDONESIA - Shidiq Ardianta (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2019)
Multilingualism is the use of more than two languages ​​in the communication process by one speaker to another. In essence multilingualism is common in heterogeneous societies, as in Indonesia, including in the world of education. The condition of bermultilingualisme that occurred in the world of education in addition to a positive effect, also has a negative effect. Positive effects that are generated from multilingualism in the world of education one of them is the creation of language diversity. Meanwhile, the negative effects that arise from multilingualism in the world of education - especially the mastery and use of foreign languages ​​- are the interference of nationalism of learners and can undermine Indonesian rules. The nationalism of learners can be eroded because there is an element of excess pride when learners use a foreign language rather than using the Indonesian language. Meanwhile, examples of foreign language interference - for example English - occur at the phrase construction level, the use of conjunctions, sentence constructions, and so on. One alternative solution to prevent the erosion of the nationalism of learners and the destruction of Indonesian rules as a result of foreign language interference (English) is to apply the method of translation. With the method of translation, learners slightly constrained dependence on foreign language mastery used as a language of instruction in books of instruction from outside and learners are always close to the Indonesian language.